2021
DOI: 10.3390/su13073908
|View full text |Cite
|
Sign up to set email alerts
|

Food Values, Satisfaction, and Loyalty: Some Evidence in Grocery Retailing Acquired during the COVID-19 Pandemic

Abstract: Recent evidence illuminates the importance of relatively new concepts in grocery retailing, such as the concept of food values. The present work aims at analyzing the influence of: (i) food values on key non-financial results, particularly satisfaction and loyalty; and (ii) satisfaction on loyalty. The paper makes a further delineation for both satisfaction and loyalty (i.e., with the product and with the grocery store), as well as considers the potential implications derived from the COVID-19 pandemic. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…According to Martínez-Ruíz and Gómez-Cantó (2016) [33], Izquierdo-Yusta et al (2020) [34] and Muro-Rodríguez et al (2021) [35], product attributes can highly influence a product choice. Consumers assign a level of importance to certain product features, which could positively or negatively affect the purchase decision process.…”
Section: Food Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Martínez-Ruíz and Gómez-Cantó (2016) [33], Izquierdo-Yusta et al (2020) [34] and Muro-Rodríguez et al (2021) [35], product attributes can highly influence a product choice. Consumers assign a level of importance to certain product features, which could positively or negatively affect the purchase decision process.…”
Section: Food Valuesmentioning
confidence: 99%
“…Such food values are emblematic of Marketing 3.0 approaches, which emphasize treating individuals as full human beings rather than as mere consumers. This is also known as the valuesdriven era because marketing decisions often try to incorporate consumers' personal values [35]. In recent years, scholars have connected food values to emotions and attitude, with the goal of enhancing the relationship between food values and purchase intention [15].…”
Section: Food Valuesmentioning
confidence: 99%
“…In another study focused on the Czech Republic, consumers were revealed to devote more attention to the nutritional value and the composition, as well as the food's origin [35]. To conclude the discussion of the studies in Europe, during the COVID-19 pandemic, a quantitative article from Spain [36] revealed that among grocery store consumers, food values have a positive and significant influence on non-financial results such as satisfaction and loyalty.…”
Section: Main Results Of the Papersmentioning
confidence: 99%
“…Finally, “Natural Food-Safe (NFS)” includes naturalness and safety and accounted for 7.859% of variance; the name of this factor corresponds to the two values it includes. The EAS factor is similar to the first factor called Consumer Ethics Value, which Muro-Rodriguez et al . (2021) identified using the same thirteen food value variables in a database collected in the context of food retailing during the pandemic (specifically collected between 15 April and 4 May 2020) in Spain.…”
Section: Empirical Researchmentioning
confidence: 87%
“…We also incorporated the two variables introduced by Bazzani et al. (2018) (novelty and animal welfare), as done by Muro-Rodriguez et al. (2021).…”
Section: Empirical Researchmentioning
confidence: 99%